KNOWLEDGE, ATTITUDES AND INTENDING PRACTICES TOWARDS EXCLUSIVE BREASTFEEDING AMONG FEMALE UNDERGRADUATES: A CROSS-SECTIONAL CASE STUDY OF MILDMAY INSTITUTE OF HEALTH SCIENCES . - Kyoyagala , Florence; Kigozi, Fred; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2023)
Background: Breastfeeding is a basic human activity that is vital to a baby‟s growth and development. Excellent breastfeeding advice from health professionals can influence a mother‟s decision to initiate and maintain breastfeeding positively. The study was aimed at assessing the knowledge, attitudes, and intended practices toward exclusive breastfeeding among female undergraduates at the Mildmay Institute of Health Sciences. Method: A mixed method cross-sectional study was performed among165full time undergraduate female students at MIHS, using convenience sampling by a structured self-administered questionnaire composed of 16 items to evaluate the students’ knowledge, 18 items to assess attitudes towards exclusive breastfeeding, 12 items to assess the intending practices and socio-demographics characteristics questions. Results: Overall, the majority (55%) of study participants had inadequate knowledge, 54.5%of the participants had positive attitudes, 44.4% were neutral and 0.6% of the respondents were less positive towards breastfeeding, a statistically significant association (p=0.019) was found between the knowledge score and the score of intending practices. Conclusions: The conducted study illustrated inadequate knowledge, positive attitudes, and inappropriate intending practices toward exclusive breastfeeding among full-time female undergraduate students at the Mildmay Institute of health sciences. Recommendations: Curricular changes aimed at promoting, supporting, protecting, and correcting the misconceptions about exclusive breastfeeding should be put in place across all levels of female undergraduates in health professions. Smart advocacy about exclusive breastfeeding should be carried out within the institute to improve the level of knowledge about exclusive breastfeeding.